Calcitonin screening in patients with thyroid nodules - Schneider, C.; Kobe, C.; Schmidt, M.; Kahraman, D.; Malchau, G.; Faust, M.; Schicha, H.; Dietlein, M. (Nuklearmedizin - NuclearMedicine, 2012)
Aim: The positive predictive value (PPV) of a slightly elevated basal calcitonin (CT) for the diagnosis of medullary thyroid cancer (MTC) is still under debate. Patients, methods: A total of 11 270 patients with thyroid nodules underwent calcitonin screening. Patients with known elevation of CT, renal insufficiency, bacterial infection, alcohol abuse, protonpump inhibitor therapy or autoimmune thyroid disease were excluded from further analysis. Serum CT was determined by the solid-phase, enzyme-labeled, two-site chemiluminescent immunoassay Immulite 2000. If possible, a pentagastrin test was done to differentiate cases of hypercalcitoninaemia. Results: Hypercalcitoninsemia was found in 32 patients. 20 patients underwent surgery. In 10 patients a MTC was found. The PPV of hyper calcitoninaemia for MTC was 31%. The PPV increased to 50% for those patients who underwent surgery (10/20). A subgroup of 26 patients presented with basal CT between 13 and 50 pg/ml, 14 of them underwent surgery, in 4 cases evidence of MTC was revealed. This resulted in a PPV of 15% (4/26), although the value increased to 28% when only surgically treated patients were considered (4/14). Conclusion: Taking all clinical data into account, calcitonin screening has an acceptable PPV for medullary thyroid cancer in patients with thyroid nodules. Therefore, we recommend calcitonin screening in centers for thyroid disorders.
Keywords: Calcitonin; screening; pentagastrin stimulation; thyroid nodule; medullary thyroid cancer